The Quest for Quality in China's Higher Education - Li, Qi (International Higher Education, 2010)
China began to enter the mass higher education era in 2002. In 2003 the Ministry of Education launched the Quality and Reform of Undergraduate Teaching and Learning Project. This project has focused on enhancing the quality of undergraduate teaching and learning by means of reforms and resource sharing. There are challenges in unaddressed conflicts of interest, unfair advantages for some applicants, and the gap between rhetoric and reality